2013
DOI: 10.1002/lary.23578
|View full text |Cite
|
Sign up to set email alerts
|

Robotic‐assisted FAMM flap for soft palate reconstruction

Abstract: The FAMM flap is reliable and easy to raise and transfer, with the surgical robot making it a good candidate for reconstruction of moderate-sized defects created by TORS applied to malignancies of the soft palate. Minor wound dehiscence is not infrequent, but reconstructive outcomes are nevertheless good. A unilateral FAMM flap will reach to the contralateral border of the uvula and is best limited to defects with a width of 2 cm or less.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 52 publications
(49 reference statements)
1
26
0
Order By: Relevance
“…The oropharyngeal surface may be reconstructed with locoregional or free flaps. Locoregional flaps such as the superior constrictor flap, the palatal island flap, the facial artery musculomucosal flap, or the submental island flap have been described for this purpose. Finally, multiple free flaps have been described for soft palate reconstruction, but the radial forearm free flap remains the mainstay of treatment .…”
Section: Discussionmentioning
confidence: 99%
“…The oropharyngeal surface may be reconstructed with locoregional or free flaps. Locoregional flaps such as the superior constrictor flap, the palatal island flap, the facial artery musculomucosal flap, or the submental island flap have been described for this purpose. Finally, multiple free flaps have been described for soft palate reconstruction, but the radial forearm free flap remains the mainstay of treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Smarrt et al demonstrated posterior pharyngeal wall flaps were feasible in three cadaveric cases [33]. Bonowitz et al used the robot to assist reconstruction of soft palatal defects using the facial artery myomucosal (FAMM) flap in five cases [34]. One advantage was better visualisation during flap dissection, however three cases experienced minor dehiscence which required surgical revision.…”
Section: Robotic Flap Surgerymentioning
confidence: 97%
“…This is a unique flap for quick, easy, low morbidity repair of mucosal defects of the mouth, lip and nose. Ten publications in the past year speak to its growing popularity, especially for palatal repair [44,46,47 …”
Section: Facial Artery Musculomucosal Flapmentioning
confidence: 99%